The role of women in the Kurdish theater, drama and media movement Erbil for example Between the 1970s and 1990s - Amin, Asst.Prof.Dr. Akram Faraidoon Hama; Bapir, Asst.Prof.Dr Zhilwan Tahir (Sulaimani Journal for Humanities, 2026)
This research entitled (The Role of Women in the Kurdish Theater, Drama and Media Movement in Erbil, for example between 1970 and 1990) focuses on the role of women and especially the role of women in Erbil at that time The importance of Kurdish theater and drama as an audiovisual media in Erbil between the years (1970-1990) which is historically considered the golden age despite many obstacles Social and political, etc., in addition to highlighting the genres of drama and theater and the importance of theater, which often finds itself in the form of educational stories, acting and performances Translated into dramatic texts and its importance in terms of education, society, politics, etc., has not been forgotten, so the characters and types have been explained and their importance has been discussed.
Keywords: Role; Women; Being; Theater; Drama; Media